2015
DOI: 10.14419/ijans.v4i2.4843
|View full text |Cite
|
Sign up to set email alerts
|

Reflective practice programme for registered nurses in training hospitals in Windhoek

Abstract: <p>Problems or incidents occurring in clinical settings are often seen as indicators of poor nursing care and even indicators of a lack of reflective practice skills. A qualitative, explorative, phenomenological, descriptive and contextual approach was conducted to explore and describe how reflective practice is practised by registered nurses in training hospitals in Windhoek. The findings revealed inadequate knowledge of reflective practice among registered nurses. Based on these findings the educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the light of the results found, the students seem to need orientation and continuous feedback to help them on their reflexive journey 12 . The awareness needs to be raised in the future professionals that daily actions should be accompanied by thoughts and reflections that grant meaning to this practice, in order to serve to improve care 13 . It is revealed that the reflexive focus in clinical tutoring helps the students, who lack professional experience, to turn these thoughts and reflections into words, which will be conscious and intentional at first but, over the years of professional experience 6 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In the light of the results found, the students seem to need orientation and continuous feedback to help them on their reflexive journey 12 . The awareness needs to be raised in the future professionals that daily actions should be accompanied by thoughts and reflections that grant meaning to this practice, in order to serve to improve care 13 . It is revealed that the reflexive focus in clinical tutoring helps the students, who lack professional experience, to turn these thoughts and reflections into words, which will be conscious and intentional at first but, over the years of professional experience 6 , 14 .…”
Section: Discussionmentioning
confidence: 99%